2015
DOI: 10.5812/jjhr.6(2)2015.24636
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Its Predictors Among Iranian Patients With Rheumatoid Arthritis: A Systematic Review

Abstract: Context: Rheumatoid Arthritis (RA) is a chronic disease accompanied by physical disabilities and a number of co-morbidities; it leads to remarkable economic burden, reduced productivity, and deteriorated quality of life (QOL). Objectives: The current study aimed to provide a clear view of quality of life among the Iranian patients with Rheumatoid Arthritis through a systematic review. Data Sources: The current study was conducted as a systematic literature review on the articles published from 2000 to 2013 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…24 Study of Van Den Ende indicated that dynamic exercise therapy has a positive effect on physical capacity 25 and has been shown to decrease the risk of heart disease, hypertension, 26 patient-reported disability and pain 27 as well as beneficial in improving symptoms and quality of life. 28 Thus, our study suggests patient self-management education to improve customer quality and ability in managing their daily problems and conditions that leads to reduction in long-term and acute complications.…”
Section: Discussionmentioning
confidence: 99%
“…24 Study of Van Den Ende indicated that dynamic exercise therapy has a positive effect on physical capacity 25 and has been shown to decrease the risk of heart disease, hypertension, 26 patient-reported disability and pain 27 as well as beneficial in improving symptoms and quality of life. 28 Thus, our study suggests patient self-management education to improve customer quality and ability in managing their daily problems and conditions that leads to reduction in long-term and acute complications.…”
Section: Discussionmentioning
confidence: 99%